2024
DOI: 10.1029/2023gl106767
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Earthquake Infragravity and Tsunami Waves With Underwater Distributed Acoustic Sensing

Han Xiao,
Zack J. Spica,
Jiaxuan Li
et al.

Abstract: Underwater Distributed Acoustic Sensing (DAS) utilizes optical fiber as a continuous sensor array. It enables high‐resolution data collection over long distances and holds promise to enhance tsunami early warning capabilities. This research focuses on detecting infragravity and tsunami waves associated with earthquakes and understanding their origin and dispersion characteristics through frequency‐wavenumber domain transformations and beamforming techniques. We propose a velocity correction method based on adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…The current values of single-channel strain noise ASD of conventional DAS equipment operating at kHz sampling frequencies suggest that these water column changes will not be easily resolved without using the information from the full array. However, beamforming methods allowing fairly large processing gains, may probably lead to enough sensitivity, as shown in recent related efforts (Xiao et al, 2024). The strain noise ASD of conventional DAS systems in this frequency range is dominated by 1/f noise caused by reference updates and laser frequency drifts.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The current values of single-channel strain noise ASD of conventional DAS equipment operating at kHz sampling frequencies suggest that these water column changes will not be easily resolved without using the information from the full array. However, beamforming methods allowing fairly large processing gains, may probably lead to enough sensitivity, as shown in recent related efforts (Xiao et al, 2024). The strain noise ASD of conventional DAS systems in this frequency range is dominated by 1/f noise caused by reference updates and laser frequency drifts.…”
Section: Discussionmentioning
confidence: 98%
“…This demonstrated that DAS can record surface gravity waves, although at much shorter periods than tsunami waves. The first, and so far only reported detection of a tsunami with seafloor DAS (Xiao et al, 2024) made use of 60 km of cable off the northwestern US coast to detect a far-field tsunami, which produced a small tsunami wave height of ∼ 6 mm at a DART station, and reaching ∼ 1 cm by the time it reached the end of the monitored fiber. Although the signal-to-noise ratio of the detected tsunami phase was low, even after beamforming, these findings underscore the feasibility of DAS technology to detect tsunami waves.…”
Section: Introductionmentioning
confidence: 99%
“…Ocean DAS records were also uploaded to a repository (Spica et al, 2023) as part of a project that collected DAS data for teleseismic events that occurred in February 2023 (Wuestefeld & Wilks, 2019). Xiao et al (2024) recently detected tsunami singals; however, DAS observations of tsunamis are still limited because they occur infrequently and their observations depend on the dates and locations of DAS experiments.…”
Section: Introductionmentioning
confidence: 99%